2014
DOI: 10.1002/cphc.201402317
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Twisting Dynamics of Thioflavin‐T: Spectroscopy of the Twisted Intramolecular Charge‐Transfer State

Abstract: Understanding the excited-state properties of thioflavin-T (ThT) has been of immense importance, because of its efficient amyloid-sensing ability related to neurodegenerative disorders. The excited-state dynamics of ThT is studied by using sub-pico- and nanosecond time-resolved transient absorption techniques as well as density functional theory (DFT)/time-dependent DFT calculations. Barrierless twisting around the central C-C bond between two aromatic moieties is the dominant process that contributes to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 57 publications
4
27
1
Order By: Relevance
“…In other words, these three compounds are not prone to TICT formations and would exhibit strong background emissions. Moreover, even though previous studies have shown that ThT could form the TICT state upon photoexcitation 33 , based on our calculations, ThT possesses a weaker push-pull strength than our designed AH-2 probe.…”
Section: Resultscontrasting
confidence: 54%
“…In other words, these three compounds are not prone to TICT formations and would exhibit strong background emissions. Moreover, even though previous studies have shown that ThT could form the TICT state upon photoexcitation 33 , based on our calculations, ThT possesses a weaker push-pull strength than our designed AH-2 probe.…”
Section: Resultscontrasting
confidence: 54%
“…From both theoretical and spectroscopic studies, the proposed behavior for the solvated dye is that the molecule is photoexcited to its lowest Franck–Condon locally excited (LE) state and then exhibits an ultrafast twisting to its excited state minimum, during which a CT to the benzothiazole group occurs. As shown in these previous studies, the excitation induces a large torsional relaxation combined with a significant bending: to quantify this distortion two angles are introduced, namely the twisting angle, φ and the bending angle, α (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorescence spectrum with maximum at 585 nm was observed by Huppert et al for ThT solution in 1-propanol at low temperatures. Ghosh and Palit demonstrated recently that intersystem crossing takes place for solutions of ThT in acetonitrile at room temperature (with low efficiency of triplet formation but readily detectable) and that triplet states population can be responsible for the fluorescence quantum yield Φ decrease. Phosphorescence and photosensitizing properties of ThT in complexes with polynucleotides were reported earlier. , Although intersystem crossing processes seem to be not very efficient for ThT in nonviscous solvents, it can be quite possible that photochemical reactions involving triplet states of ThT are responsible for ThT photodegradation and photoproducts formation observed by Hsu et al…”
Section: Introductionmentioning
confidence: 99%